If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-15+5x=2(6+x)+3
We move all terms to the left:
-15+5x-(2(6+x)+3)=0
We add all the numbers together, and all the variables
5x-(2(x+6)+3)-15=0
We calculate terms in parentheses: -(2(x+6)+3), so:We get rid of parentheses
2(x+6)+3
We multiply parentheses
2x+12+3
We add all the numbers together, and all the variables
2x+15
Back to the equation:
-(2x+15)
5x-2x-15-15=0
We add all the numbers together, and all the variables
3x-30=0
We move all terms containing x to the left, all other terms to the right
3x=30
x=30/3
x=10
| 47=7r | | 26=s/22 | | F(x)=(-50x+1200) | | 66=d/6+57 | | 1^9-2^3b=18 | | 5(y+2)=9+5y | | 3/b=7/42 | | w/22=27 | | 27=-9(y+5 | | b+84=179 | | 4j-6-2j=9-j | | -11=3k+3+4k | | 90.74=x(15-2x)(8-2x) | | 96=6(t-8) | | t-62=19 | | -5t+10=-10-9t+2t | | -2(1+5r)-(5-6r)=-35 | | 7^2x-5=3^6x-1 | | u/7-32=35 | | -5g+2.8=-8.8 | | 13.5f+14.29=11.4f-8.79+13.63 | | 17=5k2 | | 8-3y=2y-2 | | d/4+15=22 | | 18x+3=17x+7 | | (-2)/(5)p+2=(1)/(5)p+11 | | m+44/6=9 | | 10(w+3)=80 | | 31=v/5+28 | | -10=-11z-9 | | -5x-7=88 | | 20+4c=44 |